BEYOND DATA AND TECHNOLOGY: A PHILOSOPHICAL INQUIRY INTO DIGITAL AND DATA-DRIVEN EDUCATIONAL MANAGEMENT - Suheri Suheri; Nuryati Nuryati; Debi Yusuf Ardabili; Sri Nuraida Sri Nuraida; Indah Melati (Universitas Islam Negeri Mataram, 2026)
The growing reliance on digital technologies and data analytics has transformed educational management practices worldwide, positioning data-driven decision-making as a dominant managerial paradigm. While these approaches promise efficiency, transparency, and accountability, they are often grounded in technocratic and positivistic assumptions that treat data as objective, value-neutral representations of educational reality. This study aims to critically examine digital and data-driven educational management through the lens of the philosophy of science, moving beyond instrumental perspectives toward a more reflective and humanistic understanding. Employing a qualitative conceptual research design, this study conducts a critical literature analysis using an integrative philosophical framework encompassing epistemological, ontological, and axiological dimensions. The analysis reveals three key findings. First, data-driven educational management is predominantly shaped by positivistic epistemologies that privilege quantifiable indicators over contextual and professional knowledge. Second, digital management systems actively reconfigure educational reality by shaping institutional practices, governance structures, and definitions of success. Third, efficiency-oriented rationalities often overshadow ethical considerations, raising concerns about justice, responsibility, and educational values. The study contributes a novel integrative framework that positions philosophy of science as a foundational lens for understanding and guiding digital educational management. By reframing data and technology as reflective tools rather than authoritative ends, the study offers a conceptual basis for developing digital and data-driven educational management that is efficient yet ethically grounded, context-sensitive, and aligned with the broader purposes of Education.